Advances in Spatial and Temporal Databases: 13th International Symposium, SSTD 2013, Munich, Germany, August 21-23, 2013. Proceedings - Nascimento, Mario A.; Sellis, Timos; Cheng, Reynold; Sander, Jörg; Zheng, Yu; Kriegel, Hans-Peter; Renz, Matthias; Sengstock, Christian (Lecture notes in computer science, 2013)
This book constitutes the refereed proceedings of the 13th International Symposium on Spatial and Temporal Databases, SSTD 2013, held in Munich, Germany, in August 2013. The 24 revised full papers presented were carefully reviewed and selected from 58 submissions. The papers are organized in topical sections on joins and algorithms; mining and discovery; indexing; trajectories and road network data; nearest neighbours queries; uncertainty; and demonstrations
Literaturangaben
Keywords: Konferenzschrift -- 2013 -- München; Konferenzschrift; Geoinformationssystem; Abfrageverarbeitung; Räumliches Datenbanksystem; Zeitliches Datenbanksystem